Country and Industry Dynamics in Stock Returns - Catao, Luis (IMF Working Papers; Working Paper, 2003)
A perennial question in international finance is to what extent stock returns are influenced by country-location, as opposed to industry-affiliation, factors. This paper develops a novel methodology to measure these effects, in which portfolios mimicking "pure" country and industry factors are first constructed and their joint dynamics then modeled as regime-switching processes. Estimation using global firm-level data allows us to identify well-defined volatility states over the past thirty years and shows that the contribution of the industry factor becomes systematically more prominent during high global volatility states, while the country factor contribution declines. Using the model's estimates, we find that portfolio diversification possibilities vary considerably across economic states.